2020
DOI: 10.1080/2162402x.2020.1847846
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1b Study Evaluating the Safety, Tolerability, and Immunogenicity of CMB305, a Lentiviral-Based Prime-Boost Vaccine Regimen, in Patients with Locally Advanced, Relapsed, or Metastatic Cancer Expressing NY-ESO-1

Abstract: Preclinical data suggest that a "prime-boost" vaccine regimen using a target-expressing lentiviral vector for priming, followed by a recombinant protein boost, may be effective against cancer; however, this strategy has not been evaluated in a clinical setting. CMB305 is a prime-boost vaccine designed to induce a broad anti-NY-ESO-1 immune response. It is composed of LV305, which is an NY-ESO-1 expressing lentiviral vector, and G305, a recombinant adjuvanted NY-ESO-1 protein. This multicenter phase 1b, first-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…58 In an initial Phase 1 trial, CMB305 was safe and elicited antibody responses against NY-ESO-1 in 62.9% of patients and T-cell responses in 47.4%; 22.8% of patients had both. 59 A randomized Phase 2 study with the programmed death-ligand 1(PD-L1) inhibitor atezolizumab with or without CMB305 showed no statistically significant differences between the groups in OS and progression free survival (PFS), and no further study is planned with this vaccine regimen. 60 CHP-NYESO-MIS416 is a vaccine which is a polysaccharide-ligated to NY-ESO-1 used to stimulate MHC I and 2 with a T cell stimulator (MIS416), with NOD2 and TLR9 added as stimulants.…”
Section: Targeting Ctas In Ssmentioning
confidence: 99%
“…58 In an initial Phase 1 trial, CMB305 was safe and elicited antibody responses against NY-ESO-1 in 62.9% of patients and T-cell responses in 47.4%; 22.8% of patients had both. 59 A randomized Phase 2 study with the programmed death-ligand 1(PD-L1) inhibitor atezolizumab with or without CMB305 showed no statistically significant differences between the groups in OS and progression free survival (PFS), and no further study is planned with this vaccine regimen. 60 CHP-NYESO-MIS416 is a vaccine which is a polysaccharide-ligated to NY-ESO-1 used to stimulate MHC I and 2 with a T cell stimulator (MIS416), with NOD2 and TLR9 added as stimulants.…”
Section: Targeting Ctas In Ssmentioning
confidence: 99%
“…A 2011 clinical trial conducted by the National Cancer Institute was the first to report promising anticancer effects of NY-ESO-1-targeted immunotherapy in patients with metastatic synovial sarcoma using adoptively transferred autologous T-cells containing a T-cell receptor against NY-ESO-1 [46], suggesting its potential to be effective in other sarcomas as well. Since then, numerous trials targeting NY-ESO-1 in various cancer types using both adoptive T-cell therapy and vaccination approaches have concluded that there is a clear clinical benefit in pursuing NY-ESO-1 as an immunotherapeutic target [47].…”
Section: Background and Rationalementioning
confidence: 99%
“…6 In a phase Ib study of 79 patients with solid tumors that express NY-ESO-1, CMB305 vaccination resulted in the induction of anti-NY-ESO-1 antibodies and CD4 and CD8 T cells in 62.9% and 47.4% of patients, respectively, and 61.9% of patients with soft-tissue sarcomas (STS) exhibited stable disease (SD). 7…”
Section: Introductionmentioning
confidence: 99%
“…6 In a phase Ib study of 79 patients with solid tumors that express NY-ESO-1, CMB305 vaccination resulted in the induction of anti-NY-ESO-1 antibodies and CD4 and CD8 T cells in 62.9% and 47.4% of patients, respectively, and 61.9% of patients with softtissue sarcomas (STS) exhibited stable disease (SD). 7 Two sarcoma subtypes, synovial sarcoma (SS) and myxoid liposarcoma (MLS), have high frequency and homogeneity of NY-ESO-1 expression, [8][9][10][11] making these tumors most suitable for CMB305 vaccination. These translocation-associated tumors have limited treatment options, affect young adults, and have an annual incidence of 800-1,000 cases in the United States.…”
Section: Introductionmentioning
confidence: 99%